Global burden of MAFLD, MAFLD related cirrhosis and MASH related liver cancer from 1990 to 2021 - Ziwei Guo; Dongjie Wu; Runhan Mao; Ziang Yao; Qingjuan Wu; Wenliang Lv (Scientific Reports)
Abstract Metabolic dysfunction-associated fatty liver disease (MAFLD) is the most prevalent chronic liver disease globally, driven by rising obesity, metabolic syndrome (MetS), and type 2 diabetes mellitus (T2DM). This study evaluates the global, regional, and national burden of MAFLD-related diseases from 1990 to 2021 and projects future trends. Data were sourced from the Global Burden of Disease (GBD) 2021 database, including estimates for the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) associated with MAFLD, MAFLD-related cirrhosis, and MASH-related liver cancer. Countries were classified into 21 regions and five socio-demographic index (SDI) quintiles to analyze health disparities. Decomposition analyses assessed the contributions of population growth, aging, and epidemiological shifts. Future trends were modeled using the Bayesian Age-Period-Cohort (BAPC) framework. In 2021, approximately 1.27 billion MAFLD cases were reported globally, with an age-standardized prevalence rate (ASPR) of 15,018 per 100,000. The highest incidence occurred in South and East Asia. Mortality reached 138,328 cases for MAFLD and 97,403 for MAFLD-related cirrhosis. Decomposition analyses highlighted population growth and aging as key drivers. BAPC projections indicate a continued rise in MAFLD burden, particularly in low- and middle-income countries. This study underscores the increasing global burden of MAFLD and its complications. Targeted public health interventions focusing on prevention and early management are urgently needed to mitigate future impacts.